Microglial expression of CD83 governs cellular activation and restrains neuroinflammation in experimental autoimmune encephalomyelitis - Sinner, Pia; Peckert-Maier, Katrin; Mohammadian, Hashem; Kuhnt, Christine; Draßner, Christina; Panagiotakopoulou, Vasiliki; Rauber, Simon; Linnerbauer, Mathias; Haimon, Zhana; Royzman, Dmytro; Kronenberg-Versteeg, Deborah; Ramming, Andreas; et al. (Nature Communications, 2023)
Microglial activation during neuroinflammation is crucial for coordinating the immune response against neuronal tissue, and the initial response of microglia determines the severity of neuro-inflammatory diseases. The CD83 molecule has been recently shown to modulate the activation status of dendritic cells and macrophages. Although the expression of CD83 is associated with early microglia activation in various disease settings, its functional relevance for microglial biology has been elusive. Here, we describe a thorough assessment of CD83 regulation in microglia and show that CD83 expression in murine microglia is not only associated with cellular activation but also with pro-resolving functions. Using single-cell RNA-sequencing, we reveal that conditional deletion of CD83 results in an over-activated state during neuroinflammation in the experimental autoimmune encephalomyelitis model. Subsequently, CD83-deficient microglia recruit more pathogenic immune cells to the central nervous system, deteriorating resolving mechanisms and exacerbating the disease. Thus, CD83 in murine microglia orchestrates cellular activation and, consequently, also the resolution of neuroinflammation.
CRIS-Team Scopus Importer:2023-08-11